Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Media Power Point untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa di SDN Pandean Lamper 02 Semarang - Novita Arum Mandasari (Jurnal Paedagogy, 2021)
The purpose of this study was to increase student activity and learning outcomes using a problem-based learning model assisted by power point media for third grade students at SDN Pandean Lamper 02 Semarang. The research method used is classroom action research consisting of 3 cycles with 4 stages, namely planning, action, observation, and reflection. The subjects of this study were third grade students with a total of 30 people. The data collection techniques used were observation, interviews, tests, and documentation, while the data analysis techniques used descriptive analysis. The results showed that the average percentage of student activity classically increased. In the pre-cycle before treatment it was 65%, in the first cycle it was 70%, in the second cycle it was 74% while in the third cycle it was 87%. While the percentage of mastery learning outcomes in the pre-cycle is 37%, in the first cycle it is 57%, in the second cycle it is 73%, while in the third cycle it is 90%. Based on the results of the research that has been done, it can be concluded that learning in Theme 8 using a problem-based learning model assisted by power point media can improve student activities and learning outcomes.